The Role Of Digital Literacy On The Social Media Performance Of Batik MSMEs With Digital Capability As An Intervening Variable - Reza Rahmadi Hasibuan; Weni Novandari; Refius Pradipta Setyanto (International Journal of Business and Quality Research, 2024)
MSMEs are the most important pillar in the Indonesian economy. The contribution of MSMEs to the Indonesian economy with one of the MSMEs that supports the Indonesian economy is batik. Barlingmascakeb is one of the residencies that produces and sells batik throughout Indonesia. The aim of this research is to examine the influence of digital literacy on the social media performance of batik MSMEs which is mediated by digital capability. This type of research is quantitative, sampling uses purposive sampling. The number of respondents in this research was 149 Batik MSMEs who implemented digitalization and the analysis tool in this research used SmartPLS. The results of this research are that digital literacy influences social marketing performance, digital literacy influences digital capability, digital capability influences social marketing performance and digital capability mediates digital literacy on social media performance.